Potencial de bactérias endofíticas na promoção do crescimento em plantas de milho - Lobo, Laiana Lana Bentes [UNESP] (2018)
ABSTRACT – Maize is one of the most cultivated crops in the world and the current challenge is maintain productivity rates, lowering production costs and minimizing the environmental impact of the excessive use of chemical fertilizers. In this context the use of plant growth promoting bacteria can be an effective strategy for the practice of a more economic and sustainable agriculture. The present study aimed to evaluate the growth activity of endophitic bacteria of the genus Bacillus on maize plants at greenhouse and field conditions. Two experiments were carried out. The experiment I, was conducted at greenhouse, consisting of 11 treatments, ten of them containing Bacillusstrains, one of B. amyloliquefaciens, one of B. velezensis, eight of B. subtilis and one control without inoculation, arranged in a completely randomized design with three replicates. The BS-320 increased plant height, and together BS-248 promoted an increase in shoot dry matter (SDM) and root dry matter (RDM). In relation nitrogen (N) content in shoot, BS-290, BS-320 and BS-248, increased the rates of this macronutrient in root, while the content of phosphorus (P) in the roots was increased by BA-001 and BS-320. In relation to the number of colonies forming units (CFU), all isolates presented higher numbers than the control. Three isolates of B. subtilis (BS-320, BS-290 and BS-248) showed better results for the evaluated parameters at greenhouse conditions and were selected for the experiment II in the field, consisting of four treatments, three of them containing B. subtilis and a control without inoculation, arranged in a randomized block design with six replicates. In the field, BS-248 was superior to the control for the concentration of N in shoot; BS-290 increased the shoot concentration of N and P, besides P soluble in the soil and also had a greater number of Bacillus CFU in the soil compared to control. BS-320 increased the concentration P in the shoot and the yield of gains, which is so advantageous for a biological inoculant. Although the present study compared eight isolates of B. subtilis, the behavior of each isolate was different and the isolates BS-248, BS-290 and BS-320 were effective in promoting the growth of maize enabling the reduction of costs production without decrease yield and being more environmentally friendly at the same time.